LATENCY DELAY OF THE VASTUS MEDIALIS OBLIQUE AND VASTUS LATERALIS IN INDIVIDUALS WITH PATELLOFEMORAL PAIN SYNDROME - Guzmán Muñoz, Eduardo Enrique (2016)
Purpose: To determine the onset latency of the vastus medialis oblique (VMO) and vastus lateralis (VL) muscles in individuals with patellofemoral pain syndrome (PFPS). Methodology: A case-control study. Fourteen female participants with PFPS and fifteen female participants without PFPS performed a sudden lower extremity perturbation test in anterior and posterior directions. The electromyographic onset latency of the VMO and VL were measured during this test. A student’s t-test was used to compare muscle latency between the groups. Significance level was established a priori at P < 0.05. Results: During sudden anterior perturbation a significant latency delay of the VMO (p < 0.001) and VL muscles (p = 0.019) was observed in participants with PFPS. In the sudden posterior perturbation a delayed response in the activation of VMO (p = 0.023) and VL (p < 0.038) muscles was observed in individuals with PFPS. Conclusions: The results of this study indicate that individuals with PFPS have a motor deficit reflected in the latency delay of VMO and VL muscles during a sudden perturbation in the sagittal plane.